The Moriah Nightmare: Hermeneutics of the Grotesque Temptation: Мората на Морија: Херменевтика на гротескното искушение - Kulavkova, Katica; Čemerski, Ognen (Identities: Journal for Politics, Gender and Culture, 2004)
Author(s): Katica Kulavkova | Катица Ќулавкова Title (English): The Moriah Nightmare: Hermeneutics of the Grotesque Temptation Title (Macedonian): Мората на Морија: Херменевтика на гротескното искушение Translated by (Macedonian to English): Ognen Čemerski | Огнен Чемерски Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 103-127 Page Count: 24 Citation (English): Katica Kulavkova, “The Moriah Nightmare: Hermeneutics of the Grotesque Temptation,” translated from the Macedonian by Ognen Čemerski, Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004): 103-127. Citation (Macedonian): Катица Ќулавкова, „Мората на Морија: Херменевтика на гротескното искушение“, Идентитети: списание за политика, род и култура, т. 3, бр. 2 (зима 2004): 103-127.